Global Foreign Direct Investment: Structural Changes in the Current Crisis - Smirnov, Evegenii N.; Lukyanov, Sergey A. (Economy of Regions, 2021)
The current crisis, as well as complicated economic relations between countries, sustainable development risks of global value chains (GVCs), and international trade protectionism cause changes in the modern system of global foreign direct investment (FDI). Due to the complexity of these risks and the vulnerability of the world economy to future global recessions, it is necessary to develop a new concept of cross-border capital flows in the form of FDI. The research aims to identify structural changes in global FDI in the context of international trade and capital market challenges. Structural and dynamic analysis and a descriptive assessment were conducted to examine global foreign direct investment in the system of international capital movement, taking into account the unstable economic environment. A test of the impact of the current coronavirus crisis revealed that the retrospective transformation of global FDI occurred due to changes in the internationalisation of companies, cross-border mergers and acquisitions, and regional structure of FDI. Corporate disinvestment and the growing importance of intangible assets also played an important role. As a result, the slowdown in global FDI led to a decline in reinvested earnings in many economic sectors. As the long-term recovery of the world economy will be largely determined by the dynamics of global FDI, transnational companies (TNCs) should consider local crises and strive to geographically distribute capital investment. The research revealed that the differentiation of national GVC strategies and new approaches to foreign outsourcing of TNCs are the main risks of regionalisa-tion or nationalisation of global value chains and a corresponding decrease in FDI. The findings can be used to modify well-known FDI concepts, taking into account their impact on modern international economic relations.